2015
DOI: 10.1177/0333102415617415
|View full text |Cite
|
Sign up to set email alerts
|

Hypoechogenicity of brainstem raphe nuclei is associated with increased attack frequency in episodic migraine

Abstract: Sonographic findings did not differ between migraine patients and controls. Hypoechogenic BRN correlated to a higher migraine attack frequency, probably indicating more severe disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 35 publications
3
24
3
Order By: Relevance
“…Besides, MRN is also an important brain region in the human ascending arousal system, which is related with consciousness maintenance and its disorders such as fatigue and sleep disturbance [28]. In migraine patients, recent transcranial sonography studies reported that a hypoechogenic MRN correlated to a higher migraine attack frequency [46] and depression [47]. MRN is the main source of 5-hydroxytryptamine (5-HT, also known as serotonin) in the brain [48].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, MRN is also an important brain region in the human ascending arousal system, which is related with consciousness maintenance and its disorders such as fatigue and sleep disturbance [28]. In migraine patients, recent transcranial sonography studies reported that a hypoechogenic MRN correlated to a higher migraine attack frequency [46] and depression [47]. MRN is the main source of 5-hydroxytryptamine (5-HT, also known as serotonin) in the brain [48].…”
Section: Discussionmentioning
confidence: 99%
“…Hamerla et al found that reduced BR echogenicity was more often in migraine patients than in healthy controls, and proposed that this finding may be a reflection of an alteration of the serotonergic raphe nuclei [15]. In another brain sonography study, the occurrence rate of BR hypoechogenicity did not differ between migraineurs and healthy subjects, but associated with higher headache attack frequency [14]. Whereas, neither the increased occurrence rate of BR hypoechogenicity in migraineurs compared with healthy control nor the association of BR hypoechogenicity with migraine headache attack frequency was found in current study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, growing evidences indicate that comorbid depression is a risk factor for chronification of migraine and development of medication overuse headache [13]. But, up to date, it has never been reported about the association of BR alterations in TCS with depression in migraineurs, though BR hypoechogenicity has been shown to be correlated to higher headache attack frequency in migraineurs without depression in one study [14] but not in another one study [15].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, MRN is also an important brain region in the human ascending arousal system, which is related with consciousness maintenance and its disorders such as fatigue and sleep disturbance [24]. In migraine patients, recent transcranial sonography studies reported that a hypoechogenic MRN correlated to a higher migraine attack frequency [42] and depression [43]. MRN is the main source of 5-hydroxytryptamine (5-HT, also known as serotonin) in the brain [44].…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin receptors have been found on the trigeminal nerve and cranial vessels and their agonists especially triptans are effective in migraine treatment [47]. Although there is a growing body of evidence for a direct role for dysfunctions of central 5-HT and MRN availability in migraine, the exact and speci c action of endogenous 5-HT system and MRN in migraine continues to be the focus of active investigation [42,43,48].…”
Section: Discussionmentioning
confidence: 99%